Implementasi Sanksi Adat bagi Calon Mempelai dalam Pemutusan Hubungan Pertunangan (Studi Penelitian di Desa Meurandeh, Kecamatan Lembah Sabil, Kabupaten Aceh Barat Daya) - Ilka Sandela; Adella Yuana; Nila Trisna; Putri Kemala Sari (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
Engagement as a stage before marriage is expected to proceed as it should. However, along the way, various problems arise that lead to the dissolution of the engagement. If it is broken, sanctions will certainly be imposed. The purpose of this paper is to examine the implementation of customary sanctions for prospective brides and grooms in the termination of engagement in Meurandeh Village, Lembah Sabil District, Southwest Aceh Regency. The research method used is the empirical juridical method. The results of the study indicate that the implementation of sanctions is carried out according to the form of the sign given during the engagement. If the sign given in the engagement is gold, then the gold is returned to the groom (if the guilty party is a woman). However, if the guilty party is the man, then the gold is forfeited (remains the property of the woman), the man no longer has any rights to the gold. If the sign given in the engagement is a sum of money, and the guilty party is a woman, then the money given must be returned to the groom twice as much. However, if the guilty party is the man, then the money that has been given is forfeited and becomes the property of the woman. It is recommended that village customary officials strengthen the delivery of information regarding sanctions during engagements, so that prospective brides and grooms are committed to carrying out the engagement until the marriage contract and marriage.